PERAN ORGANISASI REMAS DALAM MENINGKATKAN PARTISIPASI KEGIATAN KEAGAMAAN Di MASYARAKAT (Study di Masjid Baiturrahman Kampung Peundeuy Desa Cicinde Kecamatan Banyusari Kabupaten Karawang) - Mahendra Mahendra; Tajuddin Nur; Yayat Hardiaya (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2023)
Researchers are interested in examining the role of squeezes in carrying out religious activities in the local village. The theory used in this research is adaptive strategy theory and observational social learning theory. This study uses a qualitative method with a phenomenological type. The data collection used by the researchers was interviews, observation and documentation data analysis, while the data sources in this study were the administrators and members of the Youth Mosque. The research results obtained by researchers in the field are The strategy of mosque youth in the formation of religious character through habituation to the implementation of routine religious activities is the result of research. The character of youth strategies for social welfare is shaped by habits, such as community service and helping those in need. In order to shape the character of young people, the mosque has a strategy in greeting each other and creating a conducive atmosphere. The obstacle encountered was the lack of interest of young people to participate in all youth activities in the mosque, so motivation and more interesting activities were needed to increase participation in religious activities in the community. The implication of this research is that people can know and understand that organizations are an important tool for improving people's quality of life, including social and religious life.